Peritonitis by jejunal ulcer perforation in a child: a case report - Ndèye Aby Ndoye; Ibrahima Konate; Cheikh Diouf; Mactar Dieng; Dibor Niang; Oumar Ndour; Gabriel Ngom; Ibrahima Fall (Elsevier, 2017)
Ulcer perforation is a rare cause of peritonitis in children. The cases reported in the literature are caused by peptic ulcer. We report on a case of peritonitis caused by jejunal ulcer perforation, discovered in a girl's abdomen during an acute surgical procedure. The treatment consisted of a resection of the perforation followed by an end-to-end anastomosis. Postoperative period was uneventful.